The Role of Ergonomic Interventions to Prevent Low Back Pain Among Dentists: A Scoping Review - Analdi, Jane; Wita Anggraini; Sulistyowati, Indrani; Ariyani, Annisaa Putri (Dentika: Dental Journal, 2024)
Dentists are typically at high risk of developing low back pain (LBP) due to their working position. Therefore, this study aimed to evaluate the role of ergonomic interventions in preventing LBP. The study procedures were carried out using a scoping review method with Boolean search based on PCC (Population, Concept, and Context) on PubMed, Wiley, and Google Scholar. Article management and selection process was then conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) as a guide. Inclusion criteria were experimental articles from 2011 to 2021, while exclusion criteria included scoping, rapid, and systematic reviews, gray literature, or papers that were not fully accessible. A total of 1775 articles were obtained and only 12 were selected with a total of 557 participants. The selected articles consisted of 2, 1, and 7 in the work environment, organizational, and individual domains, respectively, while 2 articles had more than 1 ergonomic intervention in different domains. The results showed that ergonomic interventions could prevent LBP among dentists. The clinical significance reported across all included articles showed that participants experienced positive changes in posture, decreased pain levels, and improved work quality after receiving the treatment across all domains.